Organic matter sedimentable without discharge of affluents in the Parcona lagoon, Ica-Peru - De la Torre-Castro, Rene Anselmo (2024)
In the oxidation ponds, there is an alarming accumulation of sedimentable organic matter, despite the absence of direct tributaries. Although the presence of potentially contaminating elements is suspected, their origin and repercussions still require clarifi cation. It is necessary to determine the organic matter to assess the value of sedimentat ion in this context. Th e study aimed to evaluate the concentration of sedimentable organic matter without effl uent discharge in the Parcona Lagoon, Ica-Peru. Th e Walkley-Black method was used to determine the organic matter in the sediments. After preparing the sample with specifi c reagents, absorbance at 590 nm was measured using a DR-5000 UV-vis spectrophotometer, with reference standards for calibration. A concentration was found at the fi ve sampling points of 3.87; 4.13; 2.96; 3.44; and 2.21 mg/kg, respectively. Th e concentration of organic matter was considered medium to very high (1.6-3.5 / 3.6-6.0), according to the Offi cial Mexican Standard NOM-021-RECNAT-2000. Th e high percentage of sedimentable organic matter, without effl uents, indicates a signifi cant accumulation of material in the environment. Th is suggests internal processes related to plant decomposition, organic residues, or biological activity, highlighting the need for proper study and management.